Structural Challenges in Zakat Management and Policy Recommendations for BAZNAS Regency/City - Citra Septiani; Ahmad Badrun Kosasih; M. Fahmi Hidayat (ASFA Foundation, 2026)
Zakat holds significant potential in alleviating poverty and improving community welfare. In Indonesia, zakat management has been increasingly professionalized through national regulations and the establishment of formal institutions such as BAZNAS and LAZ. However, the performance of BAZNAS at the regency and municipal levels remains considerably lower compared to provincial BAZNAS and other zakat institutions. This study aims to examine the key challenges faced by BAZNAS at the local level, using three primary indicators: the National Zakat Index (IZN), the Sharia Compliance Index, and the Transparency Index. The findings reveal that regency/municipal BAZNAS scores lower across macro and micro dimensions, Sharia compliance, and transparency in zakat management. These results highlight the urgent need for evidence-based policy formulation to enhance the effectiveness and professionalism of local zakat institutions. The study recommends strengthening institutional capacity, increasing support from local governments, and promoting strategic collaboration between BAZNAS and the public to build a more impactful and accountable zakat management system.